The Nature of Bias Crime Injuries: A Comparative Analysis of Physical and Psychological Victimization Effects. Issue 18 (September 2019) - Fetzer, Matthew D.; Pezzella, Frank S.
The core justification of bias crime statutes concerns whether bias-motivated crimes are qualitatively different from otherwise motivated crimes. We test the hypothesis that bias crimes are more detrimental than non-bias crimes by testing for multi-dimensional injuries to victims of bias and non-bias-motivated criminal conduct. Using National Crime Victimization Survey (NCVS) Extract 2013 Collection Year Incident-level Extract File, we analyzed physical injuries and psychological trauma to NCVS victims during 2013. We found a range of covariates consistent with the likelihood of physical injury and psychological trauma. These included whether the incident was bias motivated, whether weapons (firearms, knives, other or unknown type of weapons) were involved, whether the incident involved multiple offenders or strangers, or whether drugs or alcohol were involved. Our findings reinforce previous studies that detected empirical evidence of multi-dimensional physical and psychological injuries to bias crime victims.